Research of ways to improve the security of corporate networks - N. F. Makhmutova; E. V. Birikh; D. V. Sakharov; A. S. Krivets; M. A. Degtyarev (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The article explores a way to improve the security of a corporate network by using the technique of spoofing sender addresses when forwarding packets between computers. Method. Network traffic analysis methods, network protocol level programming and data packet processing algorithms are used. Computers on the network are connected to one server. When sending packets between computers in the network, the sender's address is replaced, and when a packet is received by another computer, the packet is disassembled, and the real sender's address is inside it. Result. The method allows for effective protection of a corporate network from attacks associated with the forgery of addresses of data packet senders. Conclusion. Using the sender address substitution technique when transmitting data in a corporate network is an effective way to increase security and protection from external threats. Further research is aimed at developing complex and reliable methods for protecting networks.